Accurate electron affinity of lanthanum atom. Issue 13 (January 2020) - Lu, Y; Tang, R; Fu, X; Ning, C
Synopsis: Atomic lanthanum anion La − is the best candidate for laser cooling of any atomic anions by far. The previous theoretical studies showed that La − has very a complicated electronic structure, which cannot be well resolved by the traditional photoelectron spectroscopy. In the present work, we used the slow-electron velocity-map imaging method in combination with an ion trap to measure the electronic structure of La − . The electron affinity of La is accurately determined to be 4496.97(20) cm −1 or 0.557553(25) eV.